Religious Tolerance among Muslim NGOs in Humanitarian Missions during the Aceh Floods from a Qur’anic Perspective - Marzatillah; Syahrizal Abbas; Kamaruzzaman Bustamam Ahmad; Syamsul Rijal; M. Firdaus Annur (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
The devastating floods that struck Aceh in late 2025 not only generated a large-scale humanitarian crisis but also reactivated latent tensions between universal humanitarian solidarity and local religious sensitivities. The presence of interfaith humanitarian actors in a region characterized by the formal implementation of Islamic law positioned humanitarian assistance within a social arena marked by complex ethical negotiations. This article examines how local Muslim NGOs interpret and practice interfaith solidarity by drawing upon the Qur’an as a living and contextual ethical framework. Employing an interpretive qualitative approach with socio-ethical analysis, the study is based on in-depth interviews, limited field observations, and the examination of secondary disaster-related data. The findings reveal that Qur’anic ethics, as enacted by Muslim NGOs, does not function as a fixed set of normative prescriptions; rather, it operates as a form of negotiated ethics continuously shaped through interactions among sacred texts, lived humanitarian experiences, and Aceh’s socio-religious environment. Interfaith solidarity is understood as a religious obligation that affirms a universal commitment to human dignity while maintaining clear ethical boundaries against the instrumentalization of humanitarian aid for non-humanitarian agendas. This study contributes to the growing scholarship on interfaith humanitarianism and Islamic ethics by offering empirical insights from a Muslim-majority context characterized by heightened religious sensitivity. It further enriches contemporary understandings of humanitarian practice as a reflective, socially embedded, and contextually negotiated ethical process.